Determination of Effective Parameters for Coal Moisture Content Determination Using a 'Design of Experiment' Method - Akkoyunlu, Mustafa Tahir; Pekel, Engin; Akkoyunlu, Mehmet Cabir; Pusat, Saban; Ozkan, Coskun; Kara, Selin Soner (TAYLOR & FRANCIS INC, 2018)
Drying of low rank coal is a very significant topic due to its high economic value. One of the most important parameter in the designing of a dryer is the exiting moisture content of the material at the specified conditions and time. Aim of this study was to utilize the design of experiment methodology to determine the most effective parameters on the moisture content of the dried coal. The investigated parameters were dryer bed height, coal particle size, inlet drying air velocity, inlet drying air temperature, inlet drying air relative humidity, exit drying air relative humidity, and time. The results showed that bed height and time were the most effective parameters, and inlet air relative humidity and inlet drying air velocity were less effective parameters. Additionally, particle size and inlet drying air temperature parameters were also significant. To attain more accurate results in the prediction of the exiting coal moisture content, only more influential parameters may be used. Therefore, the design of experiment methodology was a significant way of determining the effective parameters in the coal drying process.
Keywords: Coal; design of experiment; drying; low rank coal; moisture content; moisture estimation; SUSTAINABLE DEVELOPMENT; DRYING CHARACTERISTICS; POWER-PLANTS; FIXED-BED; PARTICLES; LIGNITE; MODEL; TEMPERATURE; KINETICS; DRYER; Energy & Fuels; Mining & Mineral Processing